Feminine images in Galician literature for children and young adults: from traditional roles to feminist novels (1975-1985) - Pena Presas, Montse (Madrygal. Revista de Estudios Gallegos, 2012)
The analysis of production of literature for children and young adults between 1975 and 1985 is decisive to visualize what kind of texts were offered to the first readers who had access to education in Galician language. In this context, studying feminine images allows us to check how the Galician literary field was reflecting those roles traditionally linked to women. However, at the same time, it becomes visible how new isolated feminine roles emerge in more innovative works as a result of the women writers’ commitment and the mark the feminist movement was leaving in literature for children and young adults.